1985
DOI: 10.3758/bf03200024
|View full text |Cite
|
Sign up to set email alerts
|

Serial anticipation and pattern extrapolation in rats as a function of element discriminability

Abstract: In Experiment 1, three groups of rats were trained on one of three serial patterns consisting of different numbers of .045-g food pellets, either the simple strong monotonic pattern 14-7-3-1-0 (Group SM) or one of two complex weak monotonic patterns, 14-5-5-1-0 (Group 5-5) or 14-9-1-1-0 (Group 1-1). Learning to anticipate the terminal O-pellet element occurred faster in Group 1-1 than in Group SM, which in turn learned faster than Group 5-5. In Experiment 2, Groups SM, 5-5, and 1-1 were trained on the first fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Second, in response to Hulse and Dorsky's (1977) rule generalization studies, Haggbloom (1985) demonstrated that pattern tracking was disrupted upon transfer only when associative information was removed, but was unaffected by manipulations that violated rule or serial position information. Finally, Haggbloom and Brooks (1985) showed that discriminability of pattern elements, not pattern structure, was the best predictor of pattern extrapolation. In subsequent studies, both camps provided additional evidence that rat sequential behavior could be described in terms of rule learning theory or item memory theory, but the debate was never adequately resolved.…”
mentioning
confidence: 99%
“…Second, in response to Hulse and Dorsky's (1977) rule generalization studies, Haggbloom (1985) demonstrated that pattern tracking was disrupted upon transfer only when associative information was removed, but was unaffected by manipulations that violated rule or serial position information. Finally, Haggbloom and Brooks (1985) showed that discriminability of pattern elements, not pattern structure, was the best predictor of pattern extrapolation. In subsequent studies, both camps provided additional evidence that rat sequential behavior could be described in terms of rule learning theory or item memory theory, but the debate was never adequately resolved.…”
mentioning
confidence: 99%
“…These results were taken as support for the RL view of pattern learning. In contrast, when Haggbloom and Brooks (1985) manipulated element discriminability, they found an instance in which a structurally more complex pattern, 14 -9 -1-1, was extrapolated better than a structurally simpler pattern, 14 -7-3-1. This latter result challenged the RL explanation of extrapolation behavior.…”
Section: Resultsmentioning
confidence: 93%
“…SPAM, as do discrimination-learning theories in general, relies on the association of items in sequence and generalization between items to account for sequential learning and extrapolation. According to Haggbloom and Brooks (1985), the memory for the 1-pellet quantity in the 7-6-1-1 pattern was a more discriminable signal of small reward or nonreward than 1 in other sequences simulated here. This results in reduced generalization from other pattern elements that would tend to signal larger rewards, and the result is that 1 in 7-6-1-1 produces anticipation of a smaller quantity-better extrapolation-than in the patterns 7-5-3-1, 7-4-4-1, and 7-3-5-1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations